Human–AI Collaboration in Socioemotional Support: Empirical Evidence of the Spontaneous Use of LLMs - Assis, Isabelle Q. G. de; Vilela, Jéssyka (Anais Estendidos do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2026: Anais Estendidos do XXI Simpósio Brasileiro de Sistemas Colaborativos, 2026)
Context: The adoption of Large Language Models (LLMs) increased human–AI interaction in emotional support settings, but their collaborative role is still unclear. Objective: We investigate LLMs' use of socioemotional support, examining user motivations, perceived benefits, and risks. Method: A Multivocal Literature Review analyzed 22 academic studies and 113 gray literature sources published between 2021 and 2025. Results: Users seek privacy, and relief from loneliness, perceiving interactions as accessible and non-judgmental; however, risks include emotional dependency, inappropriate advice, and data vulnerabilities. Conclusions: LLMs are becoming mediators of informal care, showing collaborative potential and ethical risks.